1997
DOI: 10.1097/00000539-199711000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Is Effective in Decreasing Postoperative Bleeding and Transfusions in Primary Coronary Artery Bypass Operations

Abstract: In this randomized, placebo-controlled trial, we investigated the efficacy of tranexamic acid to decrease bleeding and blood transfusions after open-heart operations. Tranexamic acid administered before and during the operation was effective in decreasing both bleeding and transfusions. When tranexamic acid was administered immediately after the operation, it had a minor beneficial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 24 publications
2
47
0
4
Order By: Relevance
“…Second, it has been accepted that the benefit of antifibrinolytic drugs as a blood conservation tool must begin prior to the start of fibrinolysis. However, in a randomized trial by Brown et al, 21 it has been shown that TA exerts similar antifibrinolytic action when administered before and during operation. Its effect remains minimal when applied after operation.…”
Section: Discussionmentioning
confidence: 97%
“…Second, it has been accepted that the benefit of antifibrinolytic drugs as a blood conservation tool must begin prior to the start of fibrinolysis. However, in a randomized trial by Brown et al, 21 it has been shown that TA exerts similar antifibrinolytic action when administered before and during operation. Its effect remains minimal when applied after operation.…”
Section: Discussionmentioning
confidence: 97%
“…18 Brown et al reported tranexamic acid preserved platelet function as measured by thromboelastogram. 12 However, as to platelet aggregation, tranexamic acid was reported to have no effect on collagen-, ADP-or thrombin-induced platelet aggregation in platelet-rich-plasma (PRP). 18 Menzies et al also reported that tranexamic acid had no effect on platelet aggregation in PRP.…”
Section: Figurementioning
confidence: 99%
“…Tranexamic acid is used to treat a variety of bleeding disorders, and to reduce postoperative blood loss in various types of surgery. Intravenously administered TXA decreases postoperative blood loss and blood transfusion requirements in patients undergoing CPB [2][3][4].…”
Section: Introductionmentioning
confidence: 99%